2012
DOI: 10.1109/tgrs.2011.2175000
|View full text |Cite
|
Sign up to set email alerts
|

Disaggregation of SMOS Soil Moisture in Southeastern Australia

Abstract: Disaggregation based on Physical And Theoretical 4 scale Change (DisPATCh) is an algorithm dedicated to the dis-5 aggregation of soil moisture observations using high-resolution 6 soil temperature data. DisPATCh converts soil temperature fields 7 into soil moisture fields given a semi-empirical soil evaporative 8 efficiency model and a first-order Taylor series expansion around 9 the field-mean soil moisture. In this study, the disaggregation 10 approach is applied to soil moisture and ocean salinity (SMOS) 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
174
2
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 214 publications
(182 citation statements)
references
References 40 publications
4
174
2
2
Order By: Relevance
“…The NSCE of the fixed window output is also greater than the coarse input NSCE for all resolutions considered, which suggests independently downscaled when the fixed window procedure is used. They are also similar to the abrupt changes observed for other methods that downscale each cell independently [Fang and Lakshmi, 2014, Merlin et al, 2013, Merlin et al, 2012.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The NSCE of the fixed window output is also greater than the coarse input NSCE for all resolutions considered, which suggests independently downscaled when the fixed window procedure is used. They are also similar to the abrupt changes observed for other methods that downscale each cell independently [Fang and Lakshmi, 2014, Merlin et al, 2013, Merlin et al, 2012.…”
Section: Resultssupporting
confidence: 84%
“…Other studies have downscaled multiple coarse grid values but have not considered this issue in depth. Several of these algorithms downscale each coarse grid cell independently from the adjacent coarse grids [Fang and Lakshmi, 2014, Merlin et al, 2013, Merlin et al, 2012, but the resulting soil moisture maps show unnatural discontinuities in the soil moisture values at the coarse grid boundaries. Such discontinuities might be problematic for applications like routing vehicles across the landscape [Flores et al, 2014].…”
Section: Perry and Niemannmentioning
confidence: 99%
“…Similar performance was observed by Molero et al [2], for which the best agreement between SMOS and the in situ data were obtained for a semiarid region. Other studies also reported better results for validating soil moisture remote sensing in semiarid land in comparison to temperate regions [45,46]. The validation of SMOS data accomplished by Molero et al [2] was completed in four study areas with different climate characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…These studies pointed out the degradation of the retrieval due to the impact of surface roughness and vegetation. Several studies suggested spatial downscaling of passive microwave soil moisture products using physical and statistical approaches (e.g., [12][13][14][15][16][17]) or by assimilating coarse scale soil moisture into a Land Data Assimilation System (LDAS) (e.g., [18]). However, few studies have demonstrated merging the active and passive microwave soil moisture [4,19] to improve the spatial and temporal availability at a moderate spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have demonstrated merging the active and passive microwave soil moisture [4,19] to improve the spatial and temporal availability at a moderate spatial resolution. The spatial downscaling using physical approaches are based on the assumption that the evaporative flux is controlled by the amount of water available in the top surface layer [12,15]. The spatial distribution of evaporative flux is computed using the visible/infrared satellite products available from the satellites such as MODIS and Landsat.…”
Section: Introductionmentioning
confidence: 99%